Efficacy and Safety of Gel Immersion Endoscopic Mucosal Resection for Non-Pedunculated Colorectal Polyps - Hiroshi Ashizawa; Kinichi Hotta; Kenichiro Imai; Sayo Ito; Yoshihiro Kishida; Kazunori Takada; Taishi Okumura; Noboru Kawata; Masao Yoshida; Yuki Maeda; Yoichi Yamamoto; Tatsunori Minamide; et al. (Life, 2023)
Underwater endoscopic mucosal resection (UEMR) has become a popular endoscopic resection method for large colorectal neoplasms. However, visualization can be poor during UEMR due to the presence of intestinal fluid. Gel immersion endoscopic mucosal resection (GIEMR), using a specially developed gel (Viscoclear®, Otsuka Pharmaceutical Factory, Tokushima, Japan), can improve the visual field. However, reports of GIEMR for colorectal polyps are limited. Herein, we evaluated the short-term outcomes of GIEMR for non-pedunculated colorectal neoplasms (NPCRN). This single-center, retrospective, and observational study includes 25 lesions in 20 patients with NPCRN who underwent GIEMR between January and October 2022. The short-term outcomes and adverse events were evaluated. The lesion locations were as follows: right colon, 18 lesions; left colon, 7 lesions; and rectum, none. The median tumor diameter was 15 (IQR, 10–18) mm. Histological classification was as follows: sessile serrated lesion, 9 cases; adenoma, 12 cases; and intramucosal adenocarcinoma, 4 cases. The overall en bloc resection rates and R0 resection rates were 80% (20/25) and 72% (18/25). For NPCRN in 10–19 mm, the en bloc resection rate was 75% (12/16), with an R0 resection rate of 69% (11/16). No post-polypectomy bleeding, perforation, or post-coagulation syndrome were observed. The findings of our study provide preliminary evidence of the efficacy and safety of GIEMR for NPCRN. Therefore, GIEMR may be a promising novel endoscopic resection method for NPCRN.